Post-EU Accession to the ECHR: The Argument for Why the ECtHR Should Abandon the Bosphorus Doctrine - Imamović, Šejla (Utrecht Journal of International and European Law, 2024)
This article analyses the case law of the ECtHR on the responsibility of the Contracting Parties following from their membership in the EU and the Court’s application of the Bosphorus presumption of equivalent protection over the period 2005–2021. It critically evaluates this presumption and the broader consequences it generates in European human rights law. The article then explores the future of the presumption in light of the case law developments and the recently relaunched negotiations on the EU’s accession to the ECHR. The summary analysis over a sixteen-year period of the Strasbourg case law demonstrates that there is a lack of methodological clarity when it comes to the parameters and the application of the Bosphorus presumption. It also shows that the mere existence of the presumption was brought into question in the case law relating to the EU principle of mutual trust. This conclusion, coupled with the recently revived aspirations for a speedy accession, suggests that the time has come for the ECtHR to abandon the Bosphorus doctrine.